Examining the Effect of Self-Rated Health on the Relationship Between Race and Racial Colorblindness in Germany - Osmar, Warsame (Journal of racial and ethnic health disparities, 2021)
This exploratory study sought to test the relationship among race, self-rated health (SRH), and colorblindness, conceptualized as the belief that race/ethnicity should not and does not matter. Independently, SRH, a multidimensional concept entailing physical and psychological health and one's affiliation in an ethnic/racial group, may contribute to racial attitudes. However, little is known about how SRH and racial/ethnic identity in combination may affect colorblind racial attitudes. It was thus hypothesized that SRH would moderate the relationship between race/ethnicity and colorblind racial attitudes. The research sample consisted of 136 autochthonous adults and "individuals with migration backgrounds" residing in Bavaria (Germany), who were divided by self-identified race (whites, n = 85; non-whites, n = 51). The results show that SRH moderates the relationship between race and racial colorblindness. More specifically, it was found that the greater the SRH of the white participants, the less they embraced a colorblind ideology. Conversely, the greater the SRH of the non-white participants, the greater their colorblind racial attitudes. These results suggest that stronger SRH may reduce colorblindness among whites and intensify it among non-whites. The implications of the obtained results may be useful in addressing how surmount barriers to data collection, measurements, and research related to racial and ethnic health disparities in "colorblind" Germany may contribute to health inequalities. Thus, this paper's contribution lies in tracking such disparities to aid their reduction or elimination.
Keywords: disparity zdravotního stavu; Moderating effect; Race Relations; Ethnicity; Race; vztahy mezi rasami; lidé; Racial Groups; diagnostické sebehodnocení; Middle Aged; mužské pohlaví; Racial colorblindness; Adult; Německo; Self-rated health; ženské pohlaví; Diagnostic Self Evaluation; Humans; Germany; lidé středního věku; dospělí; rasové skupiny; Female; Health Status Disparities; Male